2020
DOI: 10.1507/endocrj.ej19-0521
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative and anti-adipogenic effects of caffeine in an <i>in vitro</i> model of Graves’ orbitopathy

Abstract: Oxidative stress and adipogenesis play key roles in the pathogenesis of Graves' orbitopathy (GO). In this study, the therapeutic effects of caffeine on the reduction of oxidative stress and adipogenesis were evaluated in primary cultured GO orbital fibroblasts in vitro. Orbital fibroblasts were cultured from orbital connective tissues obtained from individuals with GO. Intracellular reactive oxygen species (ROS) levels induced by hydrogen peroxide or cigarette smoke extract and the expression of anti-oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 32 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Moreover, oxidative stress can disrupt the protein-folding mechanism and enhance the production of misfolded proteins, causing further ER stress (Chong et al 2017). As the state of oxidative stress has been described in GO, and inflammation and oxidative stress are central to GO pathogenesis (Ko et al 2020), the anti-oxidative effects of BiP silencing in study indicate that modulating ER stress with BiP can block the vicious cycle of oxidative stress in GO.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, oxidative stress can disrupt the protein-folding mechanism and enhance the production of misfolded proteins, causing further ER stress (Chong et al 2017). As the state of oxidative stress has been described in GO, and inflammation and oxidative stress are central to GO pathogenesis (Ko et al 2020), the anti-oxidative effects of BiP silencing in study indicate that modulating ER stress with BiP can block the vicious cycle of oxidative stress in GO.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, we have found that quercetin inhibits cigarette smoke extract-induced adipogenesis in GO fibroblasts by reducing ROS ( 48 ). Additionally, we have reported several molecules with anti-oxidative properties such as resveratrol, caffeine, and curcumin suppress adipogenesis in GO fibroblasts ( 49 51 ). Given that oxidative stress contributes to the proliferation of orbital fibroblasts ( 52 ), the impeded proliferation of GO fibroblasts by PCSK9 inhibition demonstrated in this study may be attributed to the anti-oxidative property of the PCSK9 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical setting, it is widely accepted that antioxidant effects are mostly related to age-related diseases [ 65 ], such as cardiovascular disease [ 66 , 67 ], non-alcoholic fatty liver disease [ 67 ], vascular dementia [ 68 ], Graves’ ophthalmopathy [ 69 ], cancer [ 70 , 71 ], diabetes [ 72 ], etc. ROS, including hydrogen peroxide (H 2 O 2 ), hydroxyl radical (•OH), singlet oxygen (1O 2 ), superoxide (O 2 2− ), etc., is a group of unstable molecules produced by various cells in the human body.…”
Section: Research Progress On Pharmacological Activitymentioning
confidence: 99%